Two new species of the genus Plectiscus Gravenhorst, 1829 (Hymenoptera, Ichneumonidae: Orthocentrinae) from Kenya - Varga, Oleksandr (Zootaxa, 2024)
Two new orthocentrine species of the genus Plectiscus Gravenhorst, 1829, P. oblongus sp. n. and P. taitaensis sp. n., from Kenya are described and illustrated. An identification key to Afrotropical species of the genus is provided.